2019
DOI: 10.1002/er.4549
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient steam reforming of ethanol (SRE) over CeO x grown on the nano Ni x Mg y O matrix: H 2 production under a high GHSV condition

Abstract: Summary Steam reforming of ethanol (SRE) over non‐noble metal catalysts is normally conducted at high temperature (>600°C) to thermodynamically favour the catalytic process and carbon deposition mitigation. However, high temperature inhibits water‐gas shift reaction (WGSR) and therefore restrains the yield of H2 and leads to the formation of an excessive amount of CO. The modification of non‐noble metal catalyst to enhance WGSR is an attractive alternative. In this study, CeOx was firstly loaded onto a nano‐sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…50 Between 600 and 750 °C, the reacting species are reported to be Ni 2+ ions in the outermost layer and subsurface of mixed oxide phases. 48,51 At even higher temperatures, reduction peaks are mostly ascribed to the formation of the hardly reducible NiO−MgO solid solution, 50,3,52 sometimes also referred to as Ni x Mg y O z or NiMgO x , with a variable composition depending on the sample calcination temperature and the quantity of Ni present in the material. However, even though MgO represents the vast majority of the carrier material, the high reduction temperature was attributed in the literature to the possibly formed NiAl 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…50 Between 600 and 750 °C, the reacting species are reported to be Ni 2+ ions in the outermost layer and subsurface of mixed oxide phases. 48,51 At even higher temperatures, reduction peaks are mostly ascribed to the formation of the hardly reducible NiO−MgO solid solution, 50,3,52 sometimes also referred to as Ni x Mg y O z or NiMgO x , with a variable composition depending on the sample calcination temperature and the quantity of Ni present in the material. However, even though MgO represents the vast majority of the carrier material, the high reduction temperature was attributed in the literature to the possibly formed NiAl 2 O 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the unique advantage of CeO 2 on oxygen storage, release and mobile capacity, the application of CeO 2 has attracted much attention during steam reforming process [222,223] . Luo et al [224] . adopted CeO 2 as shell to prepared CeO 2 ‐coated nano Ni x Mg y O catalysts, and found that the unique Ni 0 ‐CeO x structure is beneficial to the WGSR due to stronger CO adsorption and H 2 O activation, and inhibited methanation side reaction.…”
Section: Performance Improvement From Oxide Support Modifiedmentioning
confidence: 99%
“…Owing to the unique advantage of CeO 2 on oxygen storage, release and mobile capacity, the application of CeO 2 has attracted much attention during steam reforming process. [222,223] Luo et al [224] adopted CeO 2 as shell to prepared CeO 2 -coated nano Ni x Mg y O catalysts, and found that the unique Ni 0 -CeO x structure is beneficial to the WGSR due to stronger CO adsorption and H 2 O activation, and inhibited methanation side reaction. Li et al [225] synthetized a NiCe/MMT catalyst by ultrasonic assisted cation exchange method and demonstrated that addition of Ce species increases ethanol conversion, H 2 selectivity and catalytic stable compared with Ni/MMT.…”
Section: Ceomentioning
confidence: 99%
“…Luo et al studied the role of CeO x loaded on Ni x Mg y O matrix. 99 The highly mobile oxygen species provided by CeO x is effective for coke removal, signicantly improving the stability in SRE. Meanwhile, CeO x benets CO adsorption and promotes WGS to achieve higher H 78 The as-prepared catalyst shows good activity and stability at 650 °C.…”
Section: The Effects Of Active Metalsmentioning
confidence: 99%
“…It is difficult for one single support to possess all these advantages, so rational doping and the addition of promoters are necessary. CeO 2 is a promising candidate as promoter 78,99,100 or supports. [101][102][103] Till now, carbon deposition cannot be absolutely eliminated.…”
Section: Brief Summarymentioning
confidence: 99%